Probiotics as Adjunctive Treatment for Patients Contracted COVID-19: Current Understanding and Future Needs - Peng, Jiangying; Zhang, Meng; Yao, Guoqiang; Kwok, Lai-Yu; Zhang, Wenyi (Frontiers in Nutrition, 2021)
The coronavirus disease 2019 (COVID-19) is caused by a novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which rages all over the world and seriously threatens human life and health. Currently, there is no optimal treatment for COVID-19, and emerging evidence found that COVID-19 infection results in gut microbiota dysbiosis. The intestinal microbial richness of patients of COVID-19 does not return to normal levels even six months after recovery, but probiotic adjunctive treatment has been found to restore gut homeostasis. An updated PubMed search returned four finished clinical trials that supported the use of probiotics as adjunctive treatment for COVID-19, while at least six clinical trials aiming to investigate beneficial effects of probiotic intake in managing COVID-19 are currently in progress worldwide. Here in we tentatively summarized the understanding of the actions and potential mechanisms of probiotics in the management of COVID-19. We also highlighted some future needs for probiotic researchers in the field. The success in using probiotics as adjunctive treatment for COVID-19 has expanded the scope of application of probiotics, meanwhile deepening our knowledge in the physiological function of probiotics in modulating the gut-lung axis.